2022
DOI: 10.1155/2022/9454843
|View full text |Cite|
|
Sign up to set email alerts
|

Role and Mechanism of Epithelial-Mesenchymal Transition Mediated by Inflammatory Stress-Induced TGF-β1 in Promoting Arteriovenous Fistula Stenosis

Abstract: Objective. To explore the role and mechanism of epithelial-mesenchymal transition (EMT) mediated by inflammatory stress-induced TGF-β1 in promoting arteriovenous fistula stenosis. Methods. The inflammatory cells HK-2 were cultured by adding TGF-β1. The optimal stimulation time was determined after TGF-β1 was added. HK-2 cells were divided into two groups, DMEM/F12 medium was added to one group (the control group), and the other group was treated with TGF-β1 (10 ng/ml) in serum-free DMEM/F12 medium to stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…One possible mechanism is that the transplanted stem cells release factors or cytokines that promote angiogenesis and vasculogenesis, thereby enhancing the formation of new blood vessels in the AVF. These newly formed blood vessels may support the delivery of oxygen and nutrients to the surrounding tissues, reducing hypoxia and preventing IH formation [ 20 ]. Another possible mechanism is that UC-MSCs have immunomodulatory properties [ 21 ] which are important factors in IH development by modulating the immune response and can suppress inflammation in the vessel wall [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism is that the transplanted stem cells release factors or cytokines that promote angiogenesis and vasculogenesis, thereby enhancing the formation of new blood vessels in the AVF. These newly formed blood vessels may support the delivery of oxygen and nutrients to the surrounding tissues, reducing hypoxia and preventing IH formation [ 20 ]. Another possible mechanism is that UC-MSCs have immunomodulatory properties [ 21 ] which are important factors in IH development by modulating the immune response and can suppress inflammation in the vessel wall [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%